Comparative Evaluation of Rumen Responses, Blood and Serum Indices in Murrah Buffaloes, Vrindavani and Tharparkar Cattle on a Similar Diet - Narayana Rathode; A. K. Verma; Anju Kala; Payal Agarwal; H. Rahman; Chaudhary, L. C. (Indian Journal of Animal Nutrition, 2023)
Rumen microbial ecosystem is a complex, highly diversified microenvironment comprised of bacteria, protozoa, archaea, fungi and phages which enables ruminants to utilize poor quality fibrous feed. Comparison between cattle and buffalo for the rumen metabolism is challenging and interesting to understand.With this background information, the present study has been carried out by conducting a feeding trial of 120 days to compare rumen fermentation, microbial profile and blood indices in Murrah buffalo (n=6), Vrindavani (n=6) and Tharparkar (n=6) cattle on a similar diet. The daily dry matter intake (kg/d) was higher (P<0.001) in Murrah buffaloes and Vrindavani as compared to Tharparkar. The mean pH was significantly lower (P<0.01) in the Vrindavani cattle as compared to Murrah buffalo and Tharparkar cattle. The rumen NH3-N concentration was higher (P<0.001) in Murrah buffalo group. Whereas the total volatile fatty acid(TVFA) and propionate production was higher (P<0.05) in Vrindavani as compared to remaining two groups. With respect to the lactic acid concentration, there was no difference among the species neither at 0 nor at 2 h post feeding; however, there was a significant increase in rumen lactic acid concentration at 2 h post feeding in all the groups. The activity of rumen microbial enzymes viz., CMCase and avicelase was higher (P<0.001) in Murrah buffalo as compared to other two groups, however, amylase and protease activities were similar between Murrah buffalo and Vrindavani. The population of protozoa as assessed by microscopic counting and RT-PCR was lower (P<0.05) in Vrindavani. The population density of rumen total bacteria, fungi, methanogen and Prevotellaruminicola was similar in all the species. The number of total bacteria, total methanogens, total fungi and P.ruminicola were comparable (P>0.05) among the three groups i.e. Murrah buffalo, Vrindavani and Tharparkar cattle. The values of blood indices (bio-chemicals, enzymes) were similar in all the three groups except Hb, PCV which was higher in Murrah buffalo.